Synthesis of Non-Toxic Fe2(WO4)3 Photocatalyst with Efficient Performance - Aslam, Imran; Saqib, Muhammad; Iqbal, Muhammad W.; Boddula, Rajender; Mahmood, Tariq; Ghani, Usman (Current Analytical Chemistry, 2021)
Background: Environmental pollution has become a worldwide problem. In this regard, decontamination of wastewater and removal of organic pollutants from environment by photocatalysis has emerged as one of the most promising techniques from the last few decades. Objective: In order to degrade the harmful pollutants from wastewater, highly efficient non-toxic Fe2(WO4)3 photocatalyst was synthesized via co precipitation method. The photocatalytic activity of the as-synthesized material was examined by degrading methylene blue (MB) under various conditions. Methods: For this purpose, different experimental parameters such as catalyst load, model compound concentration, H2O2 percentage and pH value were adjusted for excellent degradation of MB, and response surface methodology (RSM) along with central composite design (CCD) as adequate model was employed for optimization process. Results: The experimental results revealed that 1.2 g/L of catalyst load, 10 g/L for dye concentration, 0.5% of H2O2 and pH 7 were found to be the optimized values for the aforesaid parameters. The optimized values led to 93% degradation of MB under UV light exposure. In addition, toxicological studies were analysed using various bioassays for both, untreated and treated samples and a conspicuous reduction (69.12%) in the toxicity level was observed. Conclusion: The study signifies that this method is useful for reclamation of water, making it useful for industry and irrigation.
Keywords: methylene blue